Unlocking User Satisfaction: An Investigation into the Effect of Perception of Ease of Use on the Peduli Lindungi Application in Jabodetabek as a Covid Digital Tracking Media - Fitriyani, Lamria; Rachmawati, Dewi (Communicare : Journal of Communication Studies, 2023)
The emergency condition of the COVID-19 pandemic which is currently being faced by various countries, including Indonesia, has made the government continue to design and evaluate various efforts that are expected to reduce the rate of spread of COVID-19. in the community, distributing vaccines to every region in Indonesia, and also continuing to carry out digital tracking through the Peduli Lindungi application. The Peduli Lindungi application provides various useful features for its users. According to data from the Ministry of Communication and Informatics, this application has been used by 32.8 million users, with an average daily addition of 500,000 users (Covid 19, 2021). However, along with the large number of users of the application, it also raises obstacles, namely because the application users care to protect is not evenly distributed. This study aims to see if there is an effect of perceived convenience on user satisfaction of Peduli Lindungi application. This research methodology uses quantitative, with the population used in this study are users of the Peduli Lindungi application in Indonesia, amounting to 32.8 million as of August 31, 2021. Data collection techniques, through the distribution of online questionnaires. The results of the study show that the perception of convenience has a strong positive effect on user satisfaction of the Peduli Lindungi application.